2012
DOI: 10.1007/s10661-012-2649-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organochlorine pesticides and plasticisers in the Selangor River basin and possible pollution sources

Abstract: A study on the quality of water abstracted for potable use was conducted in the Selangor River basin from November 2008 to July 2009. Seven sampling sites representing the intake points of water treatment plants in the basin were selected to determine the occurrence and level of 15 organochlorine pesticides (OCPs), six phthalate esters (PAEs) and bisphenol A (BPA). Results indicated OCPs were still detected regularly in 66.1 % of the samples with the Σ(15)OCPs ranging from 0.6-25.2 ng/L. The first data on PAEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Some studies have shown higher concentrations in some rivers [18][19][20]. However, the present results were similar to most of the reports on phthalate esters in source water in China and in other countries [2,[21][22][23][24][25][26][27][28][29][30]. The phthalate ester concentrations in drinking water in the present study were similar to those in previous studies [20,29,31,32] Table S3).…”
Section: Phthalate Ester Occurrence and Compositionsupporting
confidence: 90%
“…Some studies have shown higher concentrations in some rivers [18][19][20]. However, the present results were similar to most of the reports on phthalate esters in source water in China and in other countries [2,[21][22][23][24][25][26][27][28][29][30]. The phthalate ester concentrations in drinking water in the present study were similar to those in previous studies [20,29,31,32] Table S3).…”
Section: Phthalate Ester Occurrence and Compositionsupporting
confidence: 90%
“…DEHP is added to PVC material that is used in food packaging material, medical products, plastic toys, vinyl upholstery, shower curtains, adhesives, and coatings (Fernández et al 2012). Various phthalate esters have been reported to be present in the environment, including in outdoor air, water, soil, indoor air and dust, sediment, seafood and human tissue (Fernández et al 2012; Zeng et al 2011; Santhi and Mustafa 2013). As a result, during the test procedure, reducing the DEHP background that may result from reagents, utensils and instrument systems to levels as low as possible is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…In Malaysia, several studies have been recorded on the presence of organochlorine pesticides and plasticizers in a river basin [4], pharmaceuticals in surface water [5], heavy metals in freshwater [6], ammonia and manganese in drinking water treatment [7] and minerals content in drinking water [8].…”
Section: Introductionmentioning
confidence: 99%